2015
DOI: 10.1530/joe-15-0052
|View full text |Cite
|
Sign up to set email alerts
|

Dienogest reduces HSD17β1 expression and activity in endometriosis

Abstract: Endometriosis is an estrogen-dependent disease. Abnormally biosynthesized estrogens in endometriotic tissues induce the growth of the lesion and worsen endometriosis-associated pelvic pain. Dienogest (DNG), a selective progesterone receptor agonist, is widely used to treat endometriosis and efficiently relieves the symptoms. However, its pharmacological action remains unknown. In this study, we elucidated the effect of DNG on enzymes involved in local estrogen metabolism in endometriosis. Surgically obtained s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 38 publications
1
24
0
2
Order By: Relevance
“…The detailed immunostaining score for E‐cadherin, vimentin, β‐catenin and Snail is shown in Table , respectively. 17β‐hydroxysteroid dehydrogenase 1 (17β‐HSD1) is a predominant enzyme that catalyse the estrone to oestradiol (E 2 ) . In Figure B, we also detected 17β‐HSD1 mRNA levels were higher in OC compared with EU and NC.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…The detailed immunostaining score for E‐cadherin, vimentin, β‐catenin and Snail is shown in Table , respectively. 17β‐hydroxysteroid dehydrogenase 1 (17β‐HSD1) is a predominant enzyme that catalyse the estrone to oestradiol (E 2 ) . In Figure B, we also detected 17β‐HSD1 mRNA levels were higher in OC compared with EU and NC.…”
Section: Resultsmentioning
confidence: 65%
“…is a predominant enzyme that catalyse the estrone to oestradiol (E 2 ). 33,34 In Figure 1B, we also detected 17β-HSD1 mRNA levels were higher in OC compared with EU and NC.…”
Section: The Expression Of Emt Markers and 17β-hsd1 In Ovarian Endomentioning
confidence: 67%
“…In the strongly progesterone receptor (PgR) positive breast cancer cell line T-47D, progesterone, levonorgestrel, and medroxyprogesterone acetate were shown to up-regulate HSD17B1 and HSD17B5 expression and down-regulate HSD17B2 expression, with smaller effects seen on HSD17B1 expression in the moderately positive MCF7 [79]. Recently the progestin Dienogest was shown to down-regulate both HSD17B1 and aromatase expression in endometriosis patients, if this is also applicable in breast cancer remains to be seen [80]. In addition, HSD17B1 has long been known to be under the positive stimulatory influence of growth factors like insulin-like growth factors Types I and II and retinoic acid and immunological factors like interleukin 1 (IL-1), IL-6 and tumor necrosis factor α (TNFα) and it is possible that the cells of the immune system are an important source of the factors that modulate the expression and activity of HSD17B1 is breast tumors [53].…”
Section: Control Of Expression and Regulation Of Hsd17b1 And Hsd17b2mentioning
confidence: 99%
“…Accumulating evidence showed that dienogest directly inhibited progesterone receptor‐mediated cell proliferation and the production of inflammatory cytokines, toll‐like receptor 4 and nerve growth factor . Our group showed, using spheroid cultures of endometriotic stroma cells, that dienogest reduced the expression of aromatase and the expression and enzyme activity of 17ß‐HSD1, which catalyze the conversion of less potent E 1 to the more potent E 2 form in tissues . These findings suggest that dienogest comprehensively inhibits abnormal estrogen production in endometriosis.…”
Section: Aromatase‐targeting Treatment In Endometriosismentioning
confidence: 51%